A fixed-bed-column study on arsenic removal from water using an in situ-synthesized nanocomposite of magnetite and reduced graphene oxide; Nano-Structures and Nano-Objects; Vol. 41 - Galstenkova M. R. Mariya Romanovna; Mukhortova Yu. R. Yulia Ruslanovna; Pryadko A. Artyom; Botvin V. V. Vladimir Viktorovich; Wagner D. V. Dmitry; Sharonova A. A. Anna Aleksandrovna; Surmeneva M. A. Maria Alexandrovna; Surmenev R. A. Roman Anatolievich (2025, 2025)
Title screen